Finance, foreign direct investment, and Dutch disease: The case of Colombia - Alberto Botta; Antoine Godin; Marco Missaglia (Levy Economics Institute of Bard College, 2015)
In recent years, Colombia has grown relatively rapidly, but it has been a biased growth. The energy sector (the 'locomotora minero-energetica,' to use the rhetorical expression of President Juan Manuel Santos) grew much faster than the rest of the economy, while the manufacturing sector registered a negative rate of growth. These are classic symptoms of the well-known 'Dutch disease,' but our purpose here is not to establish whether or not the Dutch disease exists, but rather to shed some light on the financial viability of several, simultaneous dynamics: (1) the existence of a traditional Dutch disease being due to a large increase in mining exports and a significant exchange rate appreciation; (2) a massive increase in foreign direct investment, particularly in the mining sector; (3) a rather passive monetary policy, aimed at increasing purchasing power via exchange rate appreciation; (4) and more recently, a large distribution of dividends from Colombia to the rest of the world and the accumulation of mounting financial liabilities. The paper shows that these dynamics constitute a potential danger for the stability of the Colombian economy. Some policy recommendations are also discussed.
Keywords: F21; F32; F40; 330; Colombia; Dutch disease; Balance of payments